EP592 HE4 has a role in identifying high risk prognostic factors in endometrial cancer. (1st November 2019) - O'Toole, S; Foley, M; Rizmee, S; Norris, L; Kamran, W; Ibrahim, N; Ward, M; Thompson, C; Murphy, C; Anglim, M; D'Arcy, T; Farah, N; et al.
Abstract : Introduction/Background: Endometrial cancer (EC) is the most common gynaecological malignancy. The mainstay of treatment is surgical resection. Currently, there are no sensitive and specific biomarkers for EC. Human Epididymis protein 4 (HE4) shows promise as a diagnostic and prognostic marker. We investigated the sensitivity of preoperative serum HE4 for predicting high-risk EC. Methodology: 206 patients were recruited from the DISCOVARY bioresource between 2011 and 2016. Demographic and tumour characteristics were recorded. Preoperative serum HE4 and CA125 was measured using Fujirebio Diagnostic ELISA Kits, with the cut-off points of HE4 70 pmol/L and CA125 35 U/ml. ELISA results were correlated with clinicopathological details. Statistical analysis was performed using SPSS. Results: The cohort comprised of endometrioid adenocarcinomas (n=167) representing over 80% of the malignant cohort, carcinosarcoma (MMMT) (n=14), serous (n=17), mixed (n=6), mucinous (n=1) and clear cell (n=1). Using a cut-off of 70 pmol/L, serum HE4 had a sensitivity of 75.9% for predicting >50% myometrial invasion, more than twice the sensitivity of CA125 for >50% myometrial invasion (27.8%). Specificities were similar at 93.6% for HE4 and 95.1% for CA125. HE4 was more sensitive for predicting the presence of LVSI in EC (71%), compared to CA125 (34%). HE4 had a sensitivity of 89.6% and specificity of 46.2% for predicting lymphadenopathy, compared to a sensitivity of 46% and a specificity of 90.7% with CA125. Conclusion: HE4 showed a high sensitivity for predicting the presence of high risk prognostic factors. Clinically, HE4 may have a role in supplementing transvaginal ultrasound in EC diagnosis. Furthermore, preoperative HE4 may supplement imaging studies when stratifying EC patients as high or low risk, enabling personalisation of surgical management, and improved outcomes. Further work is needed on establishing relevant cut-offs for high-risk cohorts. Disclosure: ELISA kits were supplied by Fujirebio Diagnostics.